Freshwater fish diversity in semi‑urban artificial lakes: A case study from IPB Dramaga Campus, Indonesia - Winda Eka Putri; Muhammad Ridwan; Nur Anisa; Astihawa Indah Setiani; Rizki Rahma Hayati; Dyah Perwitasari-Farajallah (Bioma, 2026)
Fish diversity is widely used as an indicator of freshwater ecosystem stability and environmental quality, particularly in semi-urban areas experiencing increasing anthropogenic pressure. This study assessed fish diversity in three artificial lakes on the IPB University Dramaga Campus: Lake LSI, Lake SDGs, and Telaga Inspirasi. Sampling was conducted in April 2025 using a combination of active and passive capture methods. Collected specimens were identified to species level, and diversity was evaluated using the Shannon, Simpson, and evenness indices. A total of 12 fish species from nine families were recorded. Five species were introduced, with Oreochromis niloticus and Poecilia reticulata identified as the dominant taxa. Telaga Inspirasi exhibited the highest Shannon index (1.390) and the lowest Simpson value (0.733), indicating relatively high diversity and low dominance. Lake LSI supported the greatest species richness (10 species) but showed relatively high dominance (Simpson index = 0.581). Lake SDGs displayed the highest evenness value (0.610), reflecting a more balanced distribution of individuals. Environmental parameters at all sites remained within suitable ranges for fish survival. These findings highlight differences in fish community structure among lakes and emphasise the importance of ecological monitoring for freshwater biodiversity management.